Sweetly - Pearce, Jackson (Pearce, Jackson. Fairytale retellings, 2012)
When the owner of a candy shop molds magical treats that instill confidence, bravery, and passion, eighteen-year-old Gretchen's memories of her twin sister's abduction by a witch-like monster begin to fade until she learns that the danger still lurks in the forest and is looking to make Gretchen its next victim. A retelling of Hansel and Gretel.